Pengaruh Merek, Harga Dan Promosi Media Sosial Terhadap Loyalitas Pelanggan Melalui Kepuasan Konsumen Sebagai Variabel Intervening Pada Brand Skincare O.Two.O - Cinta Putri Irawan; M. Afuan; Chintya Ones Charli (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine the extent of the influence of product quality and service quality on purchasing decisions, mediated by purchase intention, at Kanopi Cafe Dharmasraya. The method employed was Structural Equation Modeling (SEM) using Partial Least Squares (PLS), with data collected via questionnaires distributed to 76 respondents. The research findings indicate the following: There is no significant influence of product quality on purchase intention at Kanopi Cafe Dharmasraya. There is no significant influence of service quality on purchase intention at Kanopi Cafe Dharmasraya. There is a significant influence of product quality on purchasing decisions at Kanopi Cafe Dharmasraya. There is no significant influence of service quality on purchasing decisions at Kanopi Cafe Dharmasraya. There is a significant influence of purchase intention on purchasing decisions at Kanopi Cafe Dharmasraya. Purchase intention does not mediate the relationship between product quality and purchasing decisions. Purchase intention does not mediate the relationship between service quality and purchasing decisions.